Arabidopsis plants overexpressing additional copies of heat shock protein Hsp101 showed high heat tolerance and endo-gene silencing. (May 2023) - Babbar, Richa; Tiwari, Lalit Dev; Mishra, Ratnesh Chandra; Shimphrui, Rinchuila; Singh, Aditya Abha; Goyal, Isha; Rana, Surbhi; Kumar, Ritesh; Sharma, Vijyesh; Tripathi, Gayatri; Khungar, Lisha; Sharma, Jaydeep; et al.
Abstract: Hsp101 chaperone is vital for survival of plants under heat stress. We generated transgenic Arabidopsis thaliana (Arabidopsis) lines with extra copies of Hsp101 gene using diverse approaches. Arabidopsis plants transformed with rice Hsp101 cDNA driven by Arabidopsis Hsp101 promoter (IN lines) showed high heat tolerance while the plants transformed with rice Hsp101 cDNA driven by CaMV35S promoter (C lines) were like wild type plants in heat stress response. Transformation of Col-0 plants with 4633 bp Hsp101 genomic fragment (GF lines) from A. thaliana containing both its coding and the regulatory sequence resulted in mostly over-expressor (OX) lines and a few under-expressor (UX) lines of Hsp101. OX lines showed enhanced heat tolerance while the UX lines were overly heat sensitive. In UX lines, silencing of not only Hsp101 endo-gene was noted but also transcript of choline kinase ( CK2 ) was silenced. Previous work established that in Arabidopsis, CK2 and Hsp101 are convergent gene pairs sharing a bidirectional promoter. The elevated AtHsp101 protein amount in most GF and IN lines was accompanied by lowered CK2 transcript levels under HS. We observed increased methylation of the promoter and gene sequence region in UX lines; however, methylation was lacking in OX lines. Highlights: Transgenic Arabidopsis generated with extra Hsp101 copies driven by its endogenous promoter had high heat tolerance than CaMV35S driven plants. Transcript of CK 2 which is convergent to Hsp101 gene sharing a bidirectional promoter, were lowered in most Hsp101 overexpressing lines. Hsp101 overexpressing lines were more efficient at solubilizing heat-induced protein aggregates than underexpressing lines or Col-0 seedlings.